Effects supplementation of novel multi-enzyme on laying performance, egg quality, and intestinal health and digestive function of laying hens - Qixin Huang; Wuzhou Yi; Jinghui Fan; Rui Chen; Xin Ma; Zhou Chen; Wenzi Wu; Lichun Qian (Poultry Science)
This study investigated the effects of multi-enzyme supplementation on various aspects of laying hens, including laying performance, egg quality, intestinal health and digestive function. In total, 384 Jingfen No.6 laying hens at 65-week-age were randomly assigned to four distinct dietary treatments: a basal diet (CON), CON supplemented with 150 g/t multi-enzyme (T1), CON with 300 g/t multi-enzyme (T2), and 600 g/t multi-enzyme (T3). A significant linear (P = 0.044) and quadratic (P = 0.014) increase was observed in the laying rate, while the feed/egg ratio exhibited a linear (P = 0.001) and quadratic (P < 0.001) decrease with increasing multi-enzyme supplementation. Additionally, linear (P < 0.05) and quadratic (P < 0.05) increases were observed in yolk rate and haugh unit with increasing levels of multi-enzyme supplementation. The trypsin activity in the duodenum and crude protein digestibility showed linear (P < 0.05) and quadratic (P < 0.05) increase with the addition of multi-enzyme. Furthermore, lipase and amylase activities in the duodenum increased quadratically (P = 0.041) and linearly (P = 0.040), respectively. Both jejunal and ileal digesta viscosities showed linear (P < 0.05) and quadratic (P < 0.05) decrease with the increasing addition of multi-enzyme. Moreover, multi-enzyme supplementation significantly increased (P < 0.05) the number of goblet cells in the intestinal of the treatment groups. The mRNA expression of Occludin-1, mucin 2 (MUC-2), large neutral amino acids transporter small subunit 1 (LAT-1) in the jejunum were significantly increased (P < 0.05) in the treatment groups (T1, T2 and T3) compared to the CON group. Additionally, the mRNA expression of solute carrier family 6-member 19 (B0AT-1) and large neutral amino acids transporter small subunit 4 (LAT-4) were significantly evaluated (P < 0.05) in the T2 and T3 groups, respectively. In conclusion, multi-enzyme supplementation enhanced digestive enzyme activities and intestinal barrier function, reduced intestinal digesta viscosity, and regulated mRNA expression of intestinal amino acid and lipid transporter genes, thereby improving crude protein digestibility and positively affecting laying performance and egg quality in hens.